Inflammatory Pseudotumor of the Liver: A Rare Case of Recurrence Following Surgical Resection - Chang, Silvia D. (EduRad, 2014)
Inflammatory pseudotumor (IPT) of the liver is a rare, benign lesion that may be mistaken for malignancy. IPTs are difficult to diagnose due to non-specific clinical, laboratory and imaging features. We report the case of a 38-year old Asian male who presented with fatigue, weight loss and hepatomegaly. He was found to have a large hepatic IPT and underwent surgical resection; approximately two and a half years later, he developed acute cholangitis secondary to IPT recurrence. We present the imaging features of hepatic IPT using ultrasound, computed tomography (CT) and magnetic resonance imaging (MRI). We also review the literature on the diagnosis and management of this disease. The unique features of this case include the IPT’s recurrence following surgical resection, large size and multiple modalities presented.